Allenes: Versatile Building Blocks in Cobalt-Catalyzed C–H Activation - Shukla, Rahul K.; Nair, Akshay M.; Volla, Chandra M. R. (Synlett, 2021)
The unique reactivity of allenes has led to their emergence as valuable coupling partners in transition-metal-mediated C–H activation reactions. On the other hand, due to its high abundance and high Lewis acidity, cobalt is garnering widespread interest as a useful catalyst for C–H activation. Here, we summarize cobalt-catalyzed C–H activations involving allenes as coupling partners and then describe our studies on Co(III)-catalyzed C-8 dienylation of quinoline N-oxides with allenes bearing a leaving group at the α-position for realizing a dienylation protocol.
Keywords: cobalt catalysis; C–H activation; allenes; dienylation; quinolines